The Moosehorn Plutonic Suite, southeastern Maine and southwestern New Brunswick:: age, petrochemistry, and tectonic setting - McLaughlin, K.; Barr, S.; Hill, M.; Thompson, M.; Ramezani, J.; Reynolds, P. (Atlantic Geology, 2003)
ABSTRACT The Moosehorn Plutonic Suite in the coastal Maine magmatic province covers an area of approximately 250 km2 in the area of Calais, Maine, and St. Stephen, New Brunswick. Based on a compilation of previous work combined with new field mapping, geochronology, and petrochemical data, the Moosehorn Plutonic Suite (MPS) is interpreted to consist mainly of five approximately contemporaneous plutons: Staples Mountain Gabbro, St. Stephen Gabbro, Calais Quartz Diorite, Baring Granite, and Elliott Mountain Diorite. The layered, sill-like Staples Mountain Gabbro is mainly mafic, whereas the larger St. Stephen Gabbro consists of a core of dunite and troctolite, surrounded by olivine gabbro and gabbro layers. The latter unit grades to quartz diorite of the Calais Quartz Diorite, the most extensive component of the MPS. The Baring Granite consists of medium-grained biotite monzogranite, which is widely mingled with quartz diorite and diorite of the Calais Quartz Diorite. The latest pluton of the MPS appears to be the Elliott Mountain Diorite, which consists mainly of texturally varied dioritic rocks. Each pluton of the MPS is interpreted to have formed by magma differentiation to produce a range of derived compositions. Evidence for mingling and mixing between magmas is also widespread in the MPS, but was not investigated during this study. A sample from the Baring Granite yielded a U-Pb (zircon) crystallization age of 421.1 ± 0.8 Ma) and phlogopite from the olivine gabbro unit of the St. Stephen Gabbro yielded a 40Ar/39Ar cooling age of 421 ± 4 Ma. The gabbroic parts of the St. Stephen Pluton and the Calais Quartz Diorite are similar in petrochemistry to mafic and intermediate parts of the Bocabec Pluton of the Saint George Batholith whereas the Baring Granite is similar to the granitic parts of the Bocabec Pluton. Plutons of the MPS generally have calc-alkalic to within-plate chemical characteristics, and their slightly negative (– 0.4) to moderately positive (+3.4) åNd values are consistent with formation by melting of primitive lower crust, such as may have been present below the Mascarene and Ellsworth terranes. Melting likely occurred in a back-arc setting related to juxtaposition in the late Silurian between these terranes and more outboard terranes of the northern Appalachian orogen.